ANALISIS FAKTOR DETERMINAN KEMENANGAN TALIBAN ATAS AMERIKA SERIKAT DI AFGHANISTAN TAHUN 2021 - Oktaviani, Mely; Saeri, Mhd. (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
20 years after being toppled in 2001, the Taliban managed to retake the Afghan government before the US troop withdrawal was complete. On August 15, 2021, the Taliban succeeded in overthrowing the government of Ashraf Ghani and taking over the government in a relatively short time. The victory of the Taliban over the US gave rise to different assumptions in the international community about the 'causes of the victory of the Taliban'. This study uses a qualitative methodology with descriptive-analytical techniques. While the data collection technique is library research, which comes from books, journals, and websites, The author divides it into three stages: data collection, data processing, and analysis of the data. The war between the US and the Taliban is an asymmetric war because there is a disparity in the status of actors (state actors and non-state actors), military strength, economic power, ideology, and structure. Even though the US was superior in terms of military and economic strength, the Taliban managed to survive and balance that power by using a guerrilla war strategy that cost the US 2 trillion USD in losses and thousands of troops. Furthermore, the Taliban took advantage of the vicious terrain, jihadist ideology, and decentralized structure. The victory of the Taliban is indeed opportunistic, which is opportunity meets preparedness. So the determinant factors that lead to victory in 2021 are because of the reduced US involvement in Afghanistan and the persistence of the Taliban. Keywords: Taliban, asymmetric warfare. Determinant Factor